Recombinant characteristics and pathogenicity of a novel PRRSV variant in weaned piglets derived from recombination of three clinical epidemic strains - Yang, Yalin; Yao, Longshuai; Wang, Xinyuan; Dong, Xinrong; Wang, Gang; Yu, Ying (Frontiers in Veterinary Science, 2024)
IntroductionThe recent emergence of PRRSV strains NADC30 and NADC34, along with their recombination with HP-PRRSV-like strains, has added complexity to PRRS control strategies on swine farms. Given the high variability and recombination potential of PRRSV, continuous monitoring of the virus’s clinical epidemiology is essential for effective prevention and control.MethodsThis study isolated a PRRSV variant, designated SDVD-NMG2023, from approximately 65-day-old pigs, showing a mortality rate of around 15% within the herd. The whole-genome, ORF5, and NSP2 sequences of the SDVD-NMG2023 isolate were aligned with 42 reference strains using MEGA software. Recombination analysis was performed using SimPlot software and RDP software. Pathogenicity analysis of SDVD-NMG2023 was conducted in four-week-old SPF Yorkshire piglets.ResultsPhylogenetic and molecular evolutionary analyses revealed a natural recombination event involving the NADC30, NADC34, and JXA1 strains. Piglets infected with SDVD-NMG2023 exhibited mild clinical symptoms, including elevated rectal temperatures in two out of five piglets, as well as cough, mild anorexia, weight stunting, interstitial pneumonia, and thymic atrophy in all cases.DiscussionThe findings indicate that the novel crossbred PRRSV isolate SDVD-NMG2023, derived from three prevalent clinical strains, may induce more unusual clinical presentations compared to those associated with HP-PRRS, albeit still impacting the health of the herd by causing immunosuppression. This study provides critical insights into the emergence of multi-strain PRRSV recombination, particularly between NADC30/34-like and HP-PRRSV-like strains, supporting a more strategic and comprehensive approach to PRRS prevention and control.